Technology brokering in action: revolutionizing the skiing and tennis industries. Issue 1 (12th January 2015) - Laudone, Robert; Liguori, Eric W.; Muldoon, Jeffrey; Bendickson, Josh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the true sources of innovation that revolutionized two sports industries – skiing and tennis, tracking the flow of ideas and power of technology brokering through the eyes of the innovator, Howard Head. Design/methodology/approach – Using a focal innovation action-set framework, the authors unite heretofore-disparate pieces of information to paint a more complete picture of the innovation and technology brokering process. Primary source material from Head's patents, personal memoirs and journals and documented correspondence between him, his brother and his colleagues are augmented with secondary source material from periodicals, media excerpts and the academic literature. Findings – Head stands as an exemplar example of a technology broker, both through his serial practice of recombinant innovation and his savvy exploitation of resources. Results discredit the Great Man Theory of Innovation, while emphasizing the importance of exploiting social capital to realize opportunities. Originality/value – This paper is the first to offer detailed insight into the technology brokering and innovation processes that revolutionized the tennis and skiing industries. It is novel in that it is one of very few papers to challenge the Great Man Theory of Innovation propagated by many textbooks and mass media, explores the process of technology brokering from the broker's perspective rather than organizationally and uses focal innovation action-set methodology to complement a historical biographical sketch of innovativeness relative to sports equipment and machines.